2020
DOI: 10.1136/bcr-2020-234727
|View full text |Cite
|
Sign up to set email alerts
|

Locked 90°-double plating of scapular spine fracture after reverse shoulder arthroplasty with union and good outcome despite plate adjacent acromion fracture

Abstract: We report the case of a 74-year-old woman who sustained a scapular spine (SS) fracture after a fall 4 weeks after reverse shoulder arthroplasty (RSA). Open reduction and internal fixation (ORIF) with locked 90°-double plating resulted in union of the SS fracture with a good outcome (subjective shoulder value: 80%; Constant score 67; 1 year) despite of an adjacent lateral acromion fracture 3 weeks after ORIF. This is the second description in the literature of a successful double plate ORIF with union of an SS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 10 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…Likewise Bauer et al chose fracture fixation in a double plate technique. 28 At the final follow-up the patient was pain free and had only slight discomfort. Debeer et al presented a patient who underwent open reduction and internal fixation (ORIF) with a single plate.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Likewise Bauer et al chose fracture fixation in a double plate technique. 28 At the final follow-up the patient was pain free and had only slight discomfort. Debeer et al presented a patient who underwent open reduction and internal fixation (ORIF) with a single plate.…”
Section: Discussionmentioning
confidence: 88%
“…Three studies with seven patients reported operative treatment. 26 – 28 Toft et al reported a case series of five patients treated with two plates in 90/90° configuration. The patients achieved a higher Constant–Murley Score (CMS) compared to the situation before the RSA implantation, but three of four patients did not reach the same mobility level as before the fall (for one patient the information was not available).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was identified from review references of the identified articles [ 29 ]. In total, nine clinical studies with 18 acromion or scapular spine fractures met the inclusion and exclusion criteria and were included in this review [ 16 , 17 , 18 , 29 , 30 , 31 , 32 , 33 , 34 ]. A detailed flow diagram of the search results is provided under Figure 2 .…”
Section: Resultsmentioning
confidence: 99%